Annual Plan 2003-04 Approved Outlay 2003-04 - Planning Commission (Planning Commission, 2003)
I am directed to refer to the discussions held in the Planning Commission between the Deputy Chairman, Planning Commission and the Chief Minister of your State on 27th March, 2003 wherein it was agreed to finalise the size of the Annual Plan 2003-04 of Arunachal Pradesh at Rs. 708.00 crores. 2. the Scheme of Financing of the agreed Annual Plan 2003-04 is given at Annexure-I. A statement showing the distribution of the agreed Annual Plan 2003-04 among different heads and sub-heads of development, including earmarked outlays and outlays for different components of PMGY, is given at Annexure-ll. 4. 1 am directed to invite your attention to the procedure for sending adjustment proposal and revision of outlays and to request you to send the adjustment proposal.
Planning Commission State Plan Division